Gender, Islam and Sexuality in Contemporary Indonesia - Arnez, Monika; Budianta, Melani (Engaging Indonesia, Critical Dialogues on Culture and Society, 2024)
This Open Access book explores the complex interplay between gender, Islam and sexuality in Indonesia, the country with the world's largest Muslim population. The authors offer a fresh look at the tensions between the local and the global through a wide range of cultural expressions and productions, including fashion, Islamic dating, popular literature, and videos on YouTube. The book is grouped around three core themes: sexuality and violence, halal lifestyle, and shame and self-determination. The first section unpacks how activists and progressive religious scholars have argued for the need for the Sexual Violence Bill and it examines the ambivalence between criminalisation and care towards LGBTQ+ people. In the second, the authors bring new insights into how local expressions of Islam, gender and sexuality are negotiated in an increasingly globalised world. The contributions on the third theme tackle gender roles and mobility in culturally diverse regions such as Hong Kong, Taiwan, Singapore, the US, and Indonesia. "The volume is a must-read for anyone wanting to get up to speed on changes in Indonesia's gender, sexuality and Islamic landscape." - Professor Sharyn Graham Davies, Director of the Herb Feith Indonesia Engagement Centre, Monash University, Australia "A showcase of excellent research, this book is of appeal to Indonesian studies scholars, and to readers in the field of Asian cultural studies. It is also of relevance to the field of Asian gender and sexuality studies, and to scholars in Islamic studies." - Professor Pamela Nilan, University of Newcastle, Australia.